Plant Diversity in Oil Palm Plantations in Tanjung Seumantoh, Karang Baru, Aceh Tamiang - Fajar Okta Widarta; Nazar Muhammad; Yaumil Istiqlal M. Nur (Universitas Syiah Kuala, 2020)
This research aims to find out the level of plant diversity in Tanjong Seumantoh, Karang Baru District, Aceh Tamiang Regency. The study used a double plot method, where the plot area for herbaceous plants was 1m x 1m and for shrubs was 5m x 5m, whereas for trees the overall density and frequency were seen. Data were analyzed using significance value (NP) analysis, diversity index, and similarity index. The results obtained 85 species of plants consisting of 55 species of herbs from 23 families, 15 species of shrubs from 9 families, and 15 species of trees from 12 families. The level of diversity of herbaceous plants in all research locations is moderate, which has an average Diversity Index of 2,620. The level of shrub diversity in all study sites is low, which has an average Diversity Index of 1.476. The family of trees that dominate the study site are Malvaceae and Arecaceae. Each of 2 species. Malvaceae consists of Hibiscus tiliaceus and Ceiba pentandra while Arecaceae consists of Arecha cathecu and Cocus nucifera.